PENGARUH RETURN ON ASSET TERHADAP NILAI PERUSAHAAN DENGAN CORPORATE SOCIAL RESPONSIBILITY DAN GOOD GOVERNANCE GOVERMENT SEBAGAI VARIABEL MODERASI PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTARDI BURSA EFEK INDONESIA TAHUN 2011-2013 - Desi Sasnita; Taufeni Taufik; Rofika - (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This research is to investigate the influence of corporate social responsibility disclosure and good corporate governance to relationship between return on asset and firm value. The population of this experiment is all of the company that is registered on BEI in 2011-2013. The taken samples are 43 company with 137 observations during three years . The used data is secondary data with collecting data method by dowloading on web BEI and literature. Analisys data method that is used on this experiment is multiple regression with helping of sofware SPSS 17.0 version.The results of this research showt hat ROA have influence to Tobins Q, with t-count 5.429, t-table 1.979, significancy 0,000. meanwhile the analysis with absolute value of the difference between test the shows that, CSR disclosure moderatein relation between ROA and Tobins Q that it shows influenence. With t-count 2.074, t-table 1.979, significancy 0,040. managerial ownership can’t moderate in relation between ROA and Tobins Q, with t-count -1.358, t-table 1.979 and significancy 0.179, Independent Commissioners can’t moderate in relation between ROA and Tobins Q with t-count -0.340, t-table 1.979, significant 0.735.Keywords: Return On Asset, Tobin’Q, Corporate Social Responsibility, managerial ownership and Independent Commissioners.